Infectious bursal disease virus inoculation infection modifies Campylobacter jejuni-host interaction in broilers - Li, Li; Pielsticker, Colin; Han, Zifeng; Kubasová, Tereza; Rychlik, Ivan; Kaspers, Bernd; Rautenschlein, Silke (Gut pathogens, 2018)
BACKGROUND: Campylobacter jejuni is considered as a chicken commensal. The gut microbiota and the immune status of the host may affect its colonization. Infectious bursal disease virus (IBDV) is an immunosuppressive virus of chickens, which allows secondary pathogens to invade or exacerbates their pathogenesis. To investigate the effect of IBDV-induced immunosuppression on the pathogenesis of C. jejuni, broiler chickens were inoculated with a very virulent (vv) strain of IBDV at 14 days post hatch followed by C. jejuni inoculation at 7 (Experiment A) or 9 (Experiment B) days post virus (IBDV) inoculation. RESULTS: vvIBDV-infection led to a depression in caecal lamina propria B lymphocytes and the anti-C. jejuni-antibody response starting at 14 days post C. jejuni inoculation (pbi). The C. jejuni-colonization pattern was comparable between mono-inoculated groups of both experiments, but it varied for vvIBDV + C. jejuni co-inoculated groups. In Experiment A significant higher numbers of colony forming units (CFU) of C. jejuni were detected in the caecum of co-inoculated birds compared to C. jejuni-mono-inoculated birds in the early phase after C. jejuni-inoculation. In Experiment B the clearance phase was affected in the co-inoculated group with significantly higher CFU at 21 days pbi compared to the mono-inoculated group (P < 0.05). No major differences were seen in numbers local lamina propria T lymphocyte populations between C. jejuni-inoculated groups with or without vvIBDV-infection. Interestingly, both pathogens affected the microbiota composition. The consequences of these microflora changes for the host have to be elucidated further. CONCLUSION: Our data suggests that the timing between viral and bacterial infection might affect the outcome of C. jejuni colonization differently. Our results confirm previous studies that anti-Campylobacter-antibodies may specifically be important for the clearance phase of the bacteria. Therefore, as vvIBDV is widely distributed in the field, it may have a significant impact on the colonization and shedding rate of C. jejuni in commercial poultry flocks. Subsequently, successful IBDV-control strategies may indirectly also benefit the gut-health of chickens.
Keywords: Immune response; Immunosuppression; Infectious bursal disease virus; Gut microbiota composition; Campylobacter jejuni